EXPLORING THE EFFECT OF EXPENSE SURGE IN THE CONSTRUCTION INDUSTRY IN CROSS RIVER STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
The construction industry in Cross River State, Nigeria, has experienced significant cost escalations, impacting project delivery and economic development. This study investigates the effects of expense surges on construction projects, focusing on cost overruns, project delays, and stakeholder dynamics. Utilizing a primary data collection approach, structured questionnaires were administered to 150 construction professionals, including contractors, engineers, and quantity surveyors, across major urban centers in Cross River State. Descriptive statistics and regression analysis revealed that inflation, exchange rate volatility, and supply chain disruptions are primary drivers of expense surges, contributing to 92% of cost overruns in public projects. The demographic analysis highlighted a predominantly male workforce, with 65% aged between 30–45 years, and varying experience levels influencing perceptions of cost management. The study identifies significant challenges, including project abandonment and compromised quality, while proposing policy interventions like inflation-indexed contracts and local material sourcing to mitigate expense surges. These findings contribute to understanding the economic pressures on Nigeria’s construction sector and offer actionable recommendations for stakeholders aiming to enhance project efficiency and sustainability.